Inclusión de estudiantes con discapacidad en las actividades recreativas de la educación básica superior en la Unidad Educativa José María Estrada - Muñoz Heleno, Gabriela Kassandra (2025)
Inclusion is the pillar of the transformation of an equitable and accessible education for all, in the area of physical education the participation of those students with disabilities represents a challenge and at the same time an opportunity to improve educational practices, that is why, the present work had as objective to design an inclusive practical guide that encourages the participation of students with disabilities in recreational activities of higher basic education in the José María Estrada Educational Unit, since, in this institution an involuntary exclusion of these students in recreational activities of physical education was witnessed due to the lack of inclusive strategies and adequate adaptations, which ends up limiting their social, motor development and their sense of belonging. The research was developed with a qualitative approach using empirical and theoretical methods under a documentary and descriptive research using as techniques direct observation, surveys to students and interviews to teachers in which questionnaires of open and closed questions were used. The results indicate that, although teachers have an inclusive vision, they are not implementing the activities effectively, therefore, not all students with disabilities manage to integrate into the activities. It was concluded that an inclusive practical guide has the potential to improve participation and promote an equitable environment in recreational activities. However, the effectiveness of these strategies will depend on ongoing teacher training.